Functional alteration of breast muscle fatty acid profile by manipulation of dietary n-6:n-3 ratios in broiler chickens - Maroufyan, Elham; Kasim, Azhar; Bejo, Mohd Hair; Loh, Teck Chwen; Farjam, Abdoreza Soleimani; Ebrahimi, Mahdi (Academic Journals, 2011)
Breast muscle fatty acid (FA) profile was studied in broiler chickens fed at different levels of n-6:n-3 polyunsaturated fatty acid (PUFA) ratios in 4 treatment groups; very high level of n-6:n-3 ratios (VH), high level of n-6:n-3 ratios (H), low level of n-6:n-3ratios (L), very low level of n-6:n-3 ratios (VL) and control, respectively. All the birds were slaughtered at 42 days of age and breast muscle were collected. FA profile of breast muscles was determined by gas liquid chromatography. Increased levels of fish oil significantly (P < 0.05) increased the long chain PUFA (LC-PUFA) n-3level, mainly because of the docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) content in the VL and L groups. n-6: n-3 ratios were effectively changed by the experimental diets. The LC- PUFA n-3 content of the VL and L groups of the breast muscle was significantly (P < 0.05) lower than in the VH, H and control groups. In conclusion, an increase in PUFAs n-3 associated with the dietary supplementation of fish oil maybe consider as a functional approach to elevate the nutritional value of chicken meat with regards to human nutrition.